Larvicidal activity of the synthesised Lignans, neolignans, and coumarin against Crocidolimia binotalis 2nd instar larvae - Juhan, Siti Fadilah; Mohd Nor, Siti Mariam; Mat Ali, Mohd Shukri; Md Nor, Siti Zulaika (University of Malaya, 2023)
Five compounds comprising of 8-O-4’-neolignan (7), two arylnaphthalene lignans (5, 8), aryldihydrobenzofuran neolignan (4), and lignan (6) were synthesised by enzymatic coupling reaction using horseradish peroxidase (HRP) between vanillin (1) with methyl ferulate (2) or methyl sinapate (3). All of these compounds, as well as previously synthesised palladium-catalysed coupling products of neolignan (9), 8-O-4'-neolignan (10), arylcoumarin (11), and lignan (12), were examined for larvicidal activityagainst Crocidolomia binotalis(C. binotalis)2ndinstar larvae. It was revealed that seven out of nine synthesised compounds had a mortality rate of more than 90% after 24 hours of exposure. Neolignan (10) and lignan (6) demonstrated strongest larvicidal activity with LD50 =2.218 mg/L and LD50 = 1.678 mg/L, respectively compared to the standard azadirachtin(LD50 =2.818 mg/L). The results showed that the synthesised compounds have a high potential for use in the control ofC. binotalislarvae and could be used in the development of new and more effective compounds as larvicides